1976
DOI: 10.1002/1097-0142(197602)37:2<620::aid-cncr2820370203>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Adriamycin, 1,3-bis (2-chloroethyl)-1-nitrosourea (BCNU-NSC 409462), and cyclophosphamide in refractory adenocarcinoma of the breast and other tumors

Abstract: Eighty-two patients with metastatic tumor received a therapeutic regimen consisting of BCNU, 100 mg/m2, and cyclophosphamide, 400 mg/m2, both intravenously on day 1, followed by adriamycin, 40 mg/m2, on day 2. Treatment was repeated every 4 weeks. Of 14 evaluable patients with adenocarcinoma of the breast, all resistant to previous chemotherapy and 12 resistant to a five-drug combination chemotherapy program, 12 had objective responses of which seven were good partial responses. Osseous, visceral, and cutaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
2002
2002

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…It is still doubtful whether and how carcinogenetic data recorded under experimental conditions in animals can quantitatively be extrapolated to the human situation. However, in contrast to common long-term bioassays in rodents that are carried out to identify cancer-causing chemicals in the environment, the doses used in the present experiment are below the actual burden in humans (Preussmann, 1975).…”
Section: Discussionmentioning
confidence: 98%
“…It is still doubtful whether and how carcinogenetic data recorded under experimental conditions in animals can quantitatively be extrapolated to the human situation. However, in contrast to common long-term bioassays in rodents that are carried out to identify cancer-causing chemicals in the environment, the doses used in the present experiment are below the actual burden in humans (Preussmann, 1975).…”
Section: Discussionmentioning
confidence: 98%
“…Such Gly-I inactivation may then help overcome drug resistance, leading to growth cessation and/or cell death in prostatic cancer cells. Moreover, clinical trials of BCNU on patients with PC were conducted more than 20 years ago (Presant et al, 1976(Presant et al, , 1980, and showed some promising outcomes. However, because no further studies have been reported since then, it is worthwhile to resume the investigation of BCNU to reevaluate its efficacy on prostatic cancer cells and to explore its cytotoxic mechanism.…”
Section: Introductionmentioning
confidence: 99%